ТЕОРЕТИЧНІ АСПЕКТИ ФОРМУВАННЯ ПІЗНАВАЛЬНОЇ АКТИВНОСТІ УЧНІВ ЗАСОБАМИ НОВИХ КОМП'ЮТЕРНИХ ТЕХНОЛОГІЙ (Педагогіка вищої та середньої школи, 2009)
The questions, which concerning of theoretical aspects of the forming of cognitive activity of personalities are considered in this article. The possibilites and categorization of new computer technology are revealed in the context of the forming the activities to cognitionю